2009
DOI: 10.1016/j.biocel.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial outer-membrane permeabilization and remodelling in apoptosis

Abstract: a b s t r a c tMany human pathologies are associated with defects in mitochondria such as diabetes, neurodegenerative diseases or cancer. This tiny organelle is involved in a plethora of processes in mammalian cells, including energy production, lipid metabolism and cell death. In the so-called intrinsic apoptotic pathway, the outer mitochondrial membrane (MOM) is premeabilized by the pro-apoptotic Bcl-2 members Bax and Bak, allowing the release of apoptogenic factors such as cytochrome c from the inter-membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 98 publications
5
63
0
6
Order By: Relevance
“…Total Bak is bound to the outer mitochondrial membrane (16) and is activated upon homodimerization induced by the same stimuli as Bax (34). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total Bak is bound to the outer mitochondrial membrane (16) and is activated upon homodimerization induced by the same stimuli as Bax (34). …”
Section: Discussionmentioning
confidence: 99%
“…We could demonstrate cytosolic distribution of cytochrome c in both CBMO and PBMO (Figure 5). However, Jourdain et al (34) suggested that only total release of cytochrome c leads to apoptosis, while a partial release might not be sufficient for caspase activation. We therefore speculate that cytochrome c release might be hampered in CBMO, possibly because of antiapoptotic distribution of Bcl-2 proteins, while in PBMO, the amount of released cytochrome c may be sufficient for apoptosis induction.…”
Section: Articlesmentioning
confidence: 99%
“…Both pathways can eventually lead to the activation of caspases and nucleases, resulting in cell apoptosis. Mitochondrial outer membrane permeabilization (MOMP), a key commitment step in the induction of cellular apoptosis, is often required for activation of the caspase proteases (26,27). It is important that the electrochemical gradient across the mitochondrial membrane collapses during the process of MOMP (28).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the presence of cardiolipin in mitochondria plays a functional role in protein interactions (Cosentino and García-Sáez 2014;Schlame et al 2000). While the compositions listed in Table 4 are obtained from healthy cells or tissues, changes in the membrane lipid compositions during apoptosis have also been well documented (Crimi and Degli Esposti 2011;Jourdain and Martinou 2009). In particular, the changes following stimulation of the extrinsic or intrinsic pathways have been compiled in various cell systems and reviewed in detail (Crimi and Degli Esposti 2011).…”
Section: The Role Of Mitochondrial Membrane Lipids In Mompmentioning
confidence: 99%